2013
DOI: 10.1097/ajp.0b013e31827b32ab
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety of Gastroretentive Gabapentin in Postherpetic Neuralgia Patients

Abstract: Long-term treatment (up to 24 wk) with G-GR of 1800 mg was well tolerated and associated with little weight gain (< 1 kg) in patients with PHN. No new safety issues emerged with G-GR long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, oral dosage forms that adopt a different conformation in the gastric cavity to prolong gastric residence time have been described over the last 30 years. These attempts have been limited, however, by lack of safety mechanisms incorporated into the dosage forms that ensure ultimate safe passage through the GI tract (57) or limited (hours) duration of the gastric residence (8), or both. Recently, we developed new materials that can potentially improve safety and have the ability to fit into ingestible forms (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oral dosage forms that adopt a different conformation in the gastric cavity to prolong gastric residence time have been described over the last 30 years. These attempts have been limited, however, by lack of safety mechanisms incorporated into the dosage forms that ensure ultimate safe passage through the GI tract (57) or limited (hours) duration of the gastric residence (8), or both. Recently, we developed new materials that can potentially improve safety and have the ability to fit into ingestible forms (9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the evaluation of long-term safety and tolerability of G-GR revealed that, after reduction in AE incidence after 2-week titration period, the frequency, intensity, and severity of AEs did not change with long-term treatment. 43 Although patients who had not previously responded to gabapentin at daily doses >1200 mg were excluded from the phase 3 studies, exclusion criteria in the phase 4 study were limited to only those in the product label; thus the integrated patient population was not enriched with patients likely to be tolerant of gabapentin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another adverse effect reported being associated with gabapentin was weight gain . However, long‐term treatment (up to 24 weeks) with gabapentin of 1800 mg was only associated with little weight gain (<1 kg) in patients with PHN …”
Section: Discussionmentioning
confidence: 99%